(untitled) (Biological Sciences - PJSIR, 1994)
Investigations were carried out to reduce cellulose and hemicellulose from mustard seed meal by diferent methods to prepared dietary fibre. Reduction in hemicellulose was found to be 28.31 % when detoxified mustard seed meal was autoclaved at 15 lbs/inclf for 30 mins. A significant reduction in cellulose and hemicellulose was also observed on treatment with sodium bicarbonate and sodium carbonate. A further reduction in these fibrous components was found on autoclaving the sodium bicarbonate or sodium carbonate treated meal. Reduction in cellulose contents was 26.45% after fermentation of detoxified meal with Trichoderma viride for 72 hrs. Protein digestibility of the meal was improved with the application of these treatments.